The molecular effects underlying the pharmacological activities of daphnetin - Zhifeng Wei; Na Wei; Long Su; Sujun Gao (Frontiers Media S.A., 2024)
As an increasingly well-known derivative of coumarin, daphnetin (7,8-dithydroxycoumarin) has demonstrated various pharmacological activities, including anti-inflammation, anti-cancer, anti-autoimmune diseases, antibacterial, organ protection, and neuroprotection properties. Various studies have been conducted to explore the action mechanisms and synthetic methods of daphnetin, given its therapeutic potential in clinical. Despite these initial insights, the precise mechanisms underlying the pharmacological activities of daphnetin remain largely unknown. In order to address this knowledge gap, we explore the molecular effects from the perspectives of signaling pathways, NOD-like receptor protein 3 (NLRP3) inflammasome and inflammatory factors; and try to find out how these mechanisms can be utilized to inform new combined therapeutic strategies.